Post Partum Pituitary Apoplexy presenting as isolated Third Cranial Nerve Palsy : A Case Report - Mukta Sharma; Aditi Prashar; Rajeev Tuli (Delhi Journal of Ophthalmology)
Pituitary apoplexy is a potential life threatening endocrine emergency caused by an acute ischemic or haemorrhagic vascular accident involving the pituitary adenoma or the adjacent pituitary gland. Patients may present with headache, double vision or rapidly worsening visual field defects. MRI plays an Important role in the diagnosis. We present a case report of post partum patient presenting with diplopia and sudden onset ptosis right eye. MRI revealed acute bleed in the pituitary gland. She was managed conservatively and the condition resolved.